SOURCES OF MOTIVATION FOR LEARNING ENGLISH OF ENGLISH EDUCATION STUDENTS IN INDONESIA - Azmy Lailiatissakinah; Arham Mauriyat (IKIP Siliwangi, 2024)
Motivation is an important factor in achieving many basic goals in a student’s academic life. This research aims to examine the sources of motivation to learn English of English education students in Indonesia. This is a survey study using a questionnaire adapted from the Attitude Motivation Test Battery (AMTB). As many as 31 respondents filled out the questionnaires, then the data were analyzed by descriptive quantitative method. Based on the findings of the research, most of the respondents have integrative as well as instrumental orientation. The data show that the most common motivation of the participants in learning English is social and cultural motivation or integrative orientation, because the respondent think that English is required make them more educated. The results suggest that teachers face the challenge of making design and implement learning methods that strengthen integrative motivation.